Brain tissue- and region-specific abnormalities on volumetric MRI scans in 21 patients with Bardet-Biedl syndrome (BBS) - Johnston Jennifer; Brinckman Danielle; Sapp Julie C; Blumhorst Catherine; Keppler-Noreuil Kim M; Nopoulos Peggy C; Biesecker Leslie G (BMC, 2011)
Abstract Background Bardet-Biedl syndrome (BBS) is a heterogeneous human disorder inherited in an autosomal recessive pattern, and characterized by the primary findings of obesity, polydactyly, hypogonadism, and learning and behavioural problems. BBS mouse models have a neuroanatomical phenotype consisting of third and lateral ventriculomegaly, thinning of the cerebral cortex, and reduction in the size of the corpus striatum and hippocampus. These abnormalities raise the question of whether humans with BBS have a characteristic morphologic brain phenotype. Further, although behavioral, developmental, neurological and motor defects have been noted in patients with BBS, to date, there are limited reports of brain findings in BBS. The present study represents the largest systematic evaluation for the presence of structural brain malformations and/or progressive changes, which may contribute to these functional problems. Methods A case-control study of 21 patients, most aged 13-35 years, except for 2 patients aged 4 and 8 years, who were diagnosed with BBS by clinical criteria and genetic analysis of known BBS genes, and were evaluated by qualitative and volumetric brain MRI scans. Healthy controls were matched 3:1 by age, sex and race. Statistical analysis was performed using SAS language with SAS STAT procedures. Results All 21 patients with BBS were found to have statistically significant region- and tissue-specific patterns of brain abnormalities. There was 1) normal intracranial volume; 2) reduced white matter in all regions of the brain, but most in the occipital region; 3) preserved gray matter volume, with increased cerebral cortex volume in only the occipital lobe; 4) reduced gray matter in the subcortical regions of the brain, including the caudate, putamen and thalamus, but not in the cerebellum; and 5) increased cerebrospinal fluid volume. Conclusions There are distinct and characteristic abnormalities in tissue- and region- specific volumes of the brain in patients with BBS, which parallel the findings, described in BBS mutant mouse models. Some of these brain abnormalities may be progressive and associated with the reported neurological and behavioral problems. Further future correlation of these MRI scan findings with detailed neurologic and neuropsychological exams together with genotype data will provide better understanding of the pathophysiology of BBS.